Preparation and Characterization of Edible Film Derived from Local Black Mulberry Pulp and Leaves - Abdul Samad, Madihah Nabilah; Basri, Hatijah (Enhanced Knowledge in Sciences and Technology, 2025)
Edible films have gained significant attention as eco-friendly packaging solutions due to their biodegradability and ability to preserve food quality. This study aimed to develop and evaluate the characterization of edible films formulated using pectin extracted from local black mulberry pulp and chlorophyll from its leaves. To enhance flexibility and mechanical strength, xanthan gum and carboxymethylcellulose (CMC) were incorporated. The films were evaluated for their characterization and antimicrobial properties to assess their suitability for food packaging applications. Scanning electron microscopy (SEM) was used to observe morphological properties, Fourier transform infrared (FTIR) spectroscopy to analyse chemical structures, and a texture analyzer to assess tensile strength. A water solubility test was conducted to evaluate dissolution properties, while antimicrobial activity was tested against Escherichia coli and Staphylococcus aureus using agar diffusion assays. The results indicated that xanthan gum enhanced the films' flexibility while CMC effectively improved tensile strength. FTIR spectra confirmed the successful integration of pectin, chlorophyll, xanthan gum, and CMC. Among all formulations, F5 exhibited the best performance, with SEM analysis revealing uniform morphology and reduced structural imperfections. It also demonstrated the highest tensile strength (29.25 MPa), extensibility (40.669 mm), and the lowest water solubility (40.04%). Antimicrobial assays showed inhibition zones of 3.3 mm for E. coli and 5.2 mm for S. aureus. This research highlights the potential of local black mulberry pulp as a source of pectin, offering a promising, sustainable solution for food packaging with enhanced functionality and environmental benefits.